2013
DOI: 10.1007/s10266-013-0126-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of background on natural tooth colour coordinates: an in vivo evaluation

Abstract: The aim of this study was to evaluate the influence of different backgrounds on spectrophotometric colour values of natural teeth. Twenty volunteers (10 males and 10 females) with a mean age of 25 years and 9 months (±3 years and 2 months) were each subjected to 4 spectrophotometric measurements of their upper right central incisor. Each sample was measured with alternatively black, 50 % grey, white or no background (positive control). DE medians ranged from 0.9 to 5.9. All artificial backgrounds presented sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
40
0
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 14 publications
2
40
0
4
Order By: Relevance
“…The use of a spectrophotometer was made to avoid all bias due to human eye evaluation, in accordance with precedent studies [6,[46][47][48] and to allow a double evaluation over a white as well as a black background. This double evaluation can simulate two different clinical situations [48]; the black background mimics class IV composite restorations, where no tooth structure exists in the back.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of a spectrophotometer was made to avoid all bias due to human eye evaluation, in accordance with precedent studies [6,[46][47][48] and to allow a double evaluation over a white as well as a black background. This double evaluation can simulate two different clinical situations [48]; the black background mimics class IV composite restorations, where no tooth structure exists in the back.…”
Section: Discussionmentioning
confidence: 99%
“…This double evaluation can simulate two different clinical situations [48]; the black background mimics class IV composite restorations, where no tooth structure exists in the back. White background can mimic the situation, where one of the walls is still present, i.e., class I, II, II, III and veneers.…”
Section: Discussionmentioning
confidence: 99%
“…Odontology recent study, Ardu and coworkers concluded that black background could be considered as the ideal background for anterior teeth compared to grey and white ones [35]. Therefore, white and black backgrounds were selected to allow a better simulation of the clinical condition, in which the black background intended to simulate the light reflectance in restorations that are not surrounded by cavity walls, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that color discrepancies might be more evident in situations in which restorations are surrounded by tooth walls [26]. These results could be explained by the difference in contrast ratio between the stained samples/background and the level of light reflectance [26,35]. Based on the testing condition applied in this in vitro study, our results showed that except for distilled water and artificial saliva, none of the materials tested had DE values below 3.3 in all other solutions.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of 28 days of immersion in the staining solutions was done in order to be consistent with the most recent literature reviews [45,46] representing around 2.5 years of clinical service. The spectrophotometric measurements with a black and a white background were done in order to simulate different clinical conditions such as class IV restorations and class III with no tooth substance is remaining (black background), or class I,II,III with some remaining tooth substance and veneers (white background) [52].…”
Section: Discussionmentioning
confidence: 99%